Rancang Bangun Mesin Pengolah Limbah Ikan Menjadi Tepung Ikan - Sedianingsih, Pony; Mooniarsih, Neilcy Tjahja; Sujana, Ivan (ELKHA : Jurnal Teknik Elektro, 2014)
Abstract– There are several place of fish auctions and fish debarkation in District of Sungai Kunyit. The fish waste that produced in District of Sungai Kunyit can reach 10 tons per day at a price of Rp 400 per kilograms up to Rp 500 per kilograms, if the fish waste is developed through the making of fish meal, it will increase the income of fishermen group that processing the fish waste. The things mentioned above become the basic consideration for the field team to do The Service Activities on Society on District of Sungai Kunyit with socialization and sequential in the making of the fish meal machine that will be a business opportunity to improve the welfare of fishermen. Producing fish meal from the fish waste need several steps, the fish waste must be drained first, and then processed through the fish meal machine. The fish meal that produced can be sold to groups of catfish farming and poultry farmers as feedstock for fish feed and animal feed. With the availability of the fish waste processing machine, hopefully it will give significant influence on the improvement of living standards, especially to fishermen groups from District of Sungai Kunyit that could ultimately increase their income. Keywords– Fishermen Groups, Fish Waste and Fish Meal.